Chapter 3 The Gibbet in the Landscape : Locating the Criminal Corpse in Mid-Eighteenth-Century England - Ward, Richard; Ward, Richard (Basingstoke Springer Nature, 2015)
Through studies of beheaded Irish traitors, smugglers hung in chains on the English coast, suicides subjected to the surgeon's knife in Dresden and the burial of executed Nazi war criminals, this volume provides a fresh perspective on the history of capital punishment. This book has two open access chapters under a CC BY license.
English
Keywords: General & world history; Modern history to 20th century: c 1700 to c 1900; Social & cultural history; Criminal or forensic psychology; International criminal law; Criminal law & procedure; capital punishment; smugglers; history; suicides; war criminals; execution; traitors; capital punishment; smugglers; history; suicides; war criminals; execution; traitors; Chichester; Gibbeting; London